The Strata-1 experiment on small body regolith segregation. (January 2018) - Fries, Marc; Abell, Paul; Brisset, Julie; Britt, Daniel; Colwell, Joshua; Dove, Adrienne; Durda, Dan; Graham, Lee; Hartzell, Christine; Hrovat, Kenneth; John, Kristen; Karrer, Dakotah; et al.
Abstract: The Strata-1 experiment studies the mixing and segregation dynamics of regolith on small bodies by exposing a suite of regolith simulants to the microgravity environment aboard the International Space Station (ISS) for one year. This will improve our understanding of regolith dynamics and properties on small asteroids, and may assist in interpreting analyses of samples from missions to small bodies such as OSIRIS-REx, Hayabusa-1 and -2, and future missions to small bodies. The Strata-1 experiment consists of four evacuated tubes partially filled with regolith simulants. The simulants are chosen to represent models of regolith covering a range of complexity and tailored to inform and improve computational studies. The four tubes are regularly imaged while moving in response to the ambient vibrational environment using dedicated cameras. The imagery is then downlinked to the Strata-1 science team about every two months. Analyses performed on the imagery includes evaluating the extent of the segregation of Strata-1 samples and comparing the observations to computational models. After Strata-1's return to Earth, x-ray tomography and optical microscopy will be used to study the post-flight simulant distribution. Strata-1 is also a pathfinder for the new "1E" ISS payload class, which is intended to simplify and accelerate emplacement of experiments on board ISS. Highlights: The Strata-1 experiment to study small-body regolith in microgravity is described. Dynamics of four regolith simulants were observed in microgravity for one year. Part of new Class1E program for small payloads on International Space Station.